Etruscanning 3D project. The 3D reconstruction of the Regolini Galassi Tomb as a research tool and a new approach in storytelling - Wim Hupperetz; Raffaele Carlani; Daniel Pletinckx; Eva Pietroni (Virtual Archaeology Review)
In the “Etruscanning3D” european project framework, the virtual reconstruction of the Regolini Galassi tomb, in Cerveteri, has been realized, in order to recontextualize its precious funerary goods, today preserved in the vatican Museums, in their ancient space, digitally represented in 3D. The reconstruction has been preceded by a huge work of data collection, reinterpretations, topographical acquisitions through a variety of techniques, digital restorations, in order to create a plausible simulation of how the tomb could appear when it was closed, at the half of the VII century BC. The final purpose of the VR application is communication inside museums, so the narrative approach and the metaphors of interactions played another key role.